PENGARUH CITRA MEREK DAN HARGA TERHADAP MINAT BELI PRODUK WARDAH PADA MAHASISWA DI DKI JAKARTA - Qonita Taqiyya, (2020)
This research is a quantitative study that aims to analyze the effect of brand image and price on buying interest in wardah products for students in DKI Jakarta. This study uses 100 students in DKI Jakarta as a sample, with a probability sampling method, namely random sampling. Data collection is done through distributing questionnaires using google form. The tool used is PLS (Partial Least Square). The results of the test show that (1) brand image has a positive influence on buying interest with a path coefficient of 0.588. (2) Price has a positive influence on buying interest with a path coefficient of 0.406.